2009
DOI: 10.1097/iae.0b013e3181b094b7
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Bevacizumab and Panretinal Photocoagulation for Proliferative Diabetic Retinopathy Associated With Vitreous Hemorrhage

Abstract: One or 2 intravitreal injections of 1.25 mg bevacizumab with PRP are associated with rapid regression of VH and may reduce the need for vitrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 26 publications
1
43
0
3
Order By: Relevance
“…In addition, many trials mentioned the prior PRP in the material and methods, but no details of any previous laser treatment were shown in the results. 33,34 IVB injection, nevertheless, seems to be a promising treatment for active PDR with previous adequate PRP. The most comparable study to ours was conducted by Jorge et al 29 who assessed IVB in persistent leaking NV, unresponsive to complete PRP, performed at least four months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many trials mentioned the prior PRP in the material and methods, but no details of any previous laser treatment were shown in the results. 33,34 IVB injection, nevertheless, seems to be a promising treatment for active PDR with previous adequate PRP. The most comparable study to ours was conducted by Jorge et al 29 who assessed IVB in persistent leaking NV, unresponsive to complete PRP, performed at least four months.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, the progression to TRD from a preexisting fibrovascular tissue contraction is a risk in few cases after intravitreal bevacizumab. 10,20,22 Furthermore, Arevalo et al reported the development or progression of TRD in 5.2% patients with severe PDR following intravitreal bevacizumab. 23 Cautious echographic examinations should be done before intravitreal bevacizumab to exclude the patients with broad vitreoretinal adhesion.…”
Section: Figmentioning
confidence: 99%
“…Anti-VEGF agents reduce the time required for vitreous clear-up and decrease the need for vitrectomy. 77,78 In most cases, bevacizumab was injected 1 week before the vitrectomy in order to avoid TRD in cases of severe PDR as discussed above. 37,45 In a recent study by the Diabetic Retinopathy Clinical Research Network, the benefit of intravitreal ranibizumab was compared with intravitreal saline injections on vitrectomy rates for vitreous haemorrhage from PDR.…”
Section: Indications Of Anti-vegf Treatment For Pdrmentioning
confidence: 99%